2003
DOI: 10.1007/s00467-003-1136-y
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia in pediatric kidney transplant recipients treated with cyclosporine

Abstract: Hyperlipidemia is a risk factor for cardiovascular disease in adult kidney transplant (Tx) recipients. We sought to determine the prevalence of, and the risk factors associated with, hyperlipidemia in pediatric kidney Tx recipients on cyclosporine (CsA). We identified 59 patients (mean age 8.2±5.7 years) transplanted between 1 January 1991 and 31 December 1993. Pre Tx, 34% had elevated total cholesterol [TC >200 mg/dl (5.17 mmol/l)]; 54% had elevated triglycerides [TG >200 mg/dl (2.26 mmol/L)]. Mean TG was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
(25 reference statements)
2
5
0
1
Order By: Relevance
“…The current investigation revealed that the common biochemical changes and adverse effects associated with cyclosporine therapy in Iraqi bone marrow transplant patients (Tables 5 and 6) were similar to that reported for Iraqi kidney transplant recipients [44,45]. Moreover, the primary biochemical changes and adverse effects of the drug reported in organ transplant patients of other nations were also identical to the present results such as electrolytes disturbances [46], hyperlipidemia [47], nephrotoxicity [48], cardiovascular risk [49], and elevation of blood pressure [50,51]. Unexpected biochemical changes and adverse effects of cyclosporine other than that found in literature and the current investigation were not registered.…”
Section: Parametersupporting
confidence: 88%
“…The current investigation revealed that the common biochemical changes and adverse effects associated with cyclosporine therapy in Iraqi bone marrow transplant patients (Tables 5 and 6) were similar to that reported for Iraqi kidney transplant recipients [44,45]. Moreover, the primary biochemical changes and adverse effects of the drug reported in organ transplant patients of other nations were also identical to the present results such as electrolytes disturbances [46], hyperlipidemia [47], nephrotoxicity [48], cardiovascular risk [49], and elevation of blood pressure [50,51]. Unexpected biochemical changes and adverse effects of cyclosporine other than that found in literature and the current investigation were not registered.…”
Section: Parametersupporting
confidence: 88%
“…found that 41% of 78 children treated with AZA, CSA, and high‐dose prednisone had elevated TC levels post‐TX (16). Mean CSA concentrations levels were significantly higher in recipients with elevated TC in this study (16). In another study of 30 transplanted children, hyperlipidemia was present in 66% (17).…”
Section: Discussionmentioning
confidence: 99%
“…A few pediatric studies have investigated the role of CSA and prednisone in post‐TX hyperlipidemia. The prevalence of elevated TC reported in these studies ranged from 41% to 66%, and elevated LDL level was found in 72–84% of TX recipients (14–20). A major risk factor for the development of post‐renal TX dyslipidemia in both adults and children is the use of certain immunosuppressive (IS) medications (11, 21–25).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Chavers ve ark. (29) 54 çocuk hastanın %54'ünde transplantasyon öncesi bakılan trigliserid düzeyini 200 mg/dl'den yüksek bulmuştur. Kronik böbrek yetmezlikli hastalarda hipertrigliserideminin yanı sıra artmış lipoprotein-A düzeyi koroner arter hastalığı için bağımsız bir risk faktörüdür (25) .…”
Section: Discussionunclassified